Renal and Glucose-Lowering Effects of Empagliflozin and Dapagliflozin in Different Chronic Kidney Disease Stages - Lin, Yi-Hsuan; Huang, Yu-Yao; Hsieh, Sheng-Hwu; Sun, Jui-Hung; Chen, Szu-Tah; Lin, Chia-Hung (Frontiers in Endocrinology, 2019)
Objective The objective of this study was to investigate the effects of sodium-glucose cotransporter 2 (SGLT2) inhibitors on renal function in different stages of chronic kidney disease (CKD). Design and Methods We conducted a retrospective cohort study using longitudinal claims data from May 2016 – December 2017 from the Chang Gung Research Database. Patients who used one of the three types of SGLT2 inhibitor available at Chang Gung Memorial Hospital, namely empagliflozin 10mg/tab (Empa10), empagliflozin 25mg/tab (Empa25), and dapagliflozin 10mg/tab (Dapa), were included, with the same number of matched non-users. Analysis of variance was used for continuous variables and the chi‐square test was applied for categorical variables. Differences in data between two groups were analyzed using an independent t-test, and the basic data before and after treatment were analyzed using generalized estimating equation (GEE). The association among renal function changes was analyzed using a Cox proportional hazards model, with the results presented as unadjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results Among the 7624 SGLT2 inhibitor users, 1696 patients used Empa10, 2654 used Empa25, and 3274 used Dapa. Compared with non-users, dapagliflozin had the lowest risk of estimated glomerular filtration rate (eGFR) decrease over 40% from baseline within 1 year (HR 0.36, 95% CI 0.25−0.51). By using the ICD-10-CM code N179, the acute kidney injury (AKI)-related hospitalization rate was lower in Empa10 and Dapa users than in non-users (HR 0.65, 95% CI 0.49−0.86). Conclusion Lower risk of eGFR decrease over 40% and AKI-related hospitalization was found in all SGLT2 inhibitor users across the different CKD stages.